2007
DOI: 10.1083/jcb.200702054
|View full text |Cite
|
Sign up to set email alerts
|

Renal defects associated with improper polarization of the CRB and DLG polarity complexes in MALS-3 knockout mice

Abstract: Kidney development and physiology require polarization of epithelia that line renal tubules. Genetic studies show that polarization of invertebrate epithelia requires the crumbs, partition-defective-3, and discs large complexes. These evolutionarily conserved protein complexes occur in mammalian kidney; however, their role in renal development remains poorly defined. Here, we find that mice lacking the small PDZ protein mammalian LIN-7c (MALS-3) have hypomorphic, cystic, and fibrotic kidneys. Proteomic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 67 publications
3
36
0
Order By: Relevance
“…CASK, which, like Pals1, contains two tandem L27 domains interacts with DLG1 through the cognate pair L27 DLG1 /L27N CASK and with Mals2 through the cognate pair L27C CASK /L27 Mals2 to form a tripartite DLG1/ CASK/Mals2 cell polarity complex ( Fig. 5A) (7,15,17,19,33). To investigate the role of CASK tandem L27 domains in the assembly of the DLG1/CASK/Mals2 ternary complex, we used strategies similar to those applied to Patj/Pals1/Mals2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CASK, which, like Pals1, contains two tandem L27 domains interacts with DLG1 through the cognate pair L27 DLG1 /L27N CASK and with Mals2 through the cognate pair L27C CASK /L27 Mals2 to form a tripartite DLG1/ CASK/Mals2 cell polarity complex ( Fig. 5A) (7,15,17,19,33). To investigate the role of CASK tandem L27 domains in the assembly of the DLG1/CASK/Mals2 ternary complex, we used strategies similar to those applied to Patj/Pals1/Mals2.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies (17,19) have shown that the symmetric L27 homotetramers (dimer of heterodimers) is a unified assembly mode for cognate pairs of type A/type B L27 domain complexes. Under physiological conditions, the L27 domain often forms a tandem L27 domain-mediated heterotrimer to achieve its biological functions as a cell polarity regulator (10,15,34). A previous study of a 4-L27 domain-containing heterotrimer from a tripartite DLG1/MPP7/Mals3 complex showed that the heterodimer of L27C MPP7 /L27 Mals3 has multiple contacts with L27 DLG1 of the L27 DLG1 /L27N MPP7 heterodimer (21), suggesting that the assembly of the L27C MPP7 /L27 Mals3 heterodimer promotes the recruitment of L27 DLG1 and further facilitates the L27 DLG1 /L27N MPP7 heterodimer formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice that carry homozygous mutations in LIN-7C [also known as MALS-3 (mammalian LIN-7) or VELI-3 (vertebrate homolog of LIN-7)], components of the Crumbs complex are either absent (Pals1 and PATJ) or strongly reduced (CRB) at the TJs of renal epithelia, whereas other TJ components, such as zona occludens 1 [ZO-1; also known as tight junction protein 1 (TJP1)], remain unaffected. As a consequence, kidney cells in mice that lack LIN-7C develop numerous cysts and fibrosis (Olsen et al, 2007). Similarly, morpholino-induced knockdown of zebrafish crb2b expression induces pronephric cysts (Omori and Malicki, 2006) and gross disorganisation of the architecture of podocytes, which are essential components of the filtration barrier of the zebrafish pronephros (Ebarasi et al, 2009 Widespread expression in many epithelia and skeletal muscles; alternatively spliced isoform Crb3b is expressed in several cell lines; Crb3b differs in its C-terminus, which terminates with -CLPI instead of -ERLI Binds to Par-6 and regulates tight junctions Crb3-CLPI localises to the cilium; knockdown results in loss of cilia; interacts with importin 1 ( …”
Section: Function Of the Crumbs Complex In Vertebrate Cellsmentioning
confidence: 99%
“…In particular, the L27 domain of LIN7 is known to mediate heterodimerisation with L27 domain-containing membrane-associated guanylate kinase (MAGUK) proteins, including calcium/calmodulin-dependent serine protein kinase (CASK), protein associated with LIN7 (Pals), synapse-associated protein 97 (SAP97) and isoforms of PSD-95 and PSD-93 (Chetkovich et al, 2002;Feng et al, 2004;Funke et al, 2005), which form the core of protein complexes that mediate synaptic development, plasticity, and functionality (Zheng et al, 2011). In vertebrates, there are three genes, LIN7-A-B-C also named MALS/Veli-1-2-3, and alterations in these genes cause renal defects and synaptic dysfunctions (Olsen et al, 2007), and mice harbouring null mutations of all the three LIN7 isoforms die perinatally with respiratory problems and impaired synaptic transmission (Olsen et al, 2005). Moreover, polymorphisms and altered expression of LIN7 have been recently associated with human psychiatric conditions such as attention-deficit/ hyperactivity disorder (ADHD) and neurodegenerative diseases (Lanktree et al, 2008;Zucker et al, 2010;Shinawi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%